Oxford handbook of small superconductors - Narlikar, A. V., 1940- (Oxford handbooks., 2017)
"This handbook is about a remarkable set of materials that are technically referred to as 'mesoscopic superconductors', which for all practical purposes are tiny or small in their dimensions, ranging from a few micrometers down to a nanometer. At this level of smallness, the superconducting properties are dramatically changed, showing the dominance of quantum effects. Ground breaking research studies of small superconductors have emerged, and in a world obsessed with miniaturization of electronic device technology, small superconductors acquire even greater relevance and timeliness for the development of exciting novel quantum devices. The chapters, contributed by noted researchers and frontrunners in the field from 15 countries, are presented in three parts, namely progress in basic studies, materials specific research, and advances in nanodevices. The contents of the handbook should be of immediate interest to advanced level university students and researchers particularly in physics, materials science, nanoscience and engineering departments. Various reviews and overviews appearing in the book should answer the queries and curiosities of non-specialists interested in nanoscale superconductivity. At the start, the book carries an extended introduction for readers new to the field. The book should also appeal to scientists and engineers from electronic industries interested in knowing the current status of the theory, manufacture, and future of mesoscopic superconductors. In doing so, this volume offers the opportunity to engage with cutting edge research in one of the most exciting fields of physics today and tomorrow"--Provided by publisher.